NICOTINE REPLACEMENT THERAPY OF THE TOBACCO ADDICTION IN PREVENTION OF CARDIORESPIRATORY DISEASES - M. G. Gambaryan (Столичная издательская компания, 2015)
Tobacco smoking is a serious public health issue in Russia and one of the major risk factors of cardiorespiratory diseases. Smoking cessation is the most cost-effective measure for prevention of cardiovascular and respiratory diseases and for reduction in risk of death from these diseases. Helping the patients to quit smoking is difficult because of the nicotine addiction that most of them face. Nicotine replacement therapy (NRT) is used to reduce the tobacco dependence and withdrawal symptoms while quitting smoking and ease the transition from cigarette smoking to complete abstinence. NRT doubles the chances of smokers for quitting. Among modern pharmacotherapy approaches for smoking cessation NRT is a method of choice in cardiovascular and respiratory patients due to proven safety. NRT with a combination of slowand long-acting drugs with rapid-acting ones is more effective than NRT with a single type of drugs and helps to overcome the withdrawal symptoms and withstand tobacco dependence in a longer run. NRT may be successfully used as a pharmaceutical aid for patients with tobacco dependence in the hospitals when those will adopt the smoke-free hospitals status under the new Federal "antitobacco" law.